Antiseizure medication-induced obsessive-compulsive disorder and tic disorder: a pragmatic review. (3rd August 2022) - Doobay, Minakshi; Sharma, Verinder; Eccles, Heidi
ABSTRACT: Introduction: With a lifetime prevalence of 2.3%, obsessive compulsive disorder is a chronic, disabling condition that is associated with significant social and occupational impairment. Up to 30% of individuals with obsessive-compulsive disorder have a lifetime diagnosis of tic disorders. Antiseizure medication is increasingly used for a variety of physical and psychiatric illnesses. Clarification of the relationship between these symptoms/disorders and use of antiseizure medication is critically important for diagnostic and treatment purposes. Areas covered: Studies on antiseizure-induced obsessive-compulsive disorder and tic disorders are reviewed. The literature search strategy identified 89 articles. Twenty-nine articles were included in the final results. Of these, 24 are case reports or case studies, 2 cross-sectional studies, 1 chart review, 1 population-based case-control study and 1 observational prospective study assessing lamotrigine, levetiracetam, topiramate, zonisamide, and carbamazepine. Expert opinion: This study highlighted the temporal relationship of antiseizure medication use and onset of obsessive-compulsive symptoms and tics. Monitoring for medication-induced obsessive compulsions or tics should be undertaken when prescribing antiseizure medication for treatment of mood disorders or epilepsy. Further research identifying the causal relationship between antiseizure medication and de novo onset of obsessive-compulsive symptoms, obsessive-compulsive disorder and tic disorder is required.